Perioperative lumbar plexus block and cardiac ischemia in patients with hip fracture: randomized clinical trial - Altermatt,Fernando R. (2018)
Abstract Background Perioperative myocardial ischemia is common among patients undergoing hip fracture surgery. Our aim is to evaluate the efficacy of perioperative continuous lumbar plexus block in reducing the risk of cardiac ischemic events of elderly patients undergoing surgery for hip fractures, expressed as a reduction of ischemic events per subject. Methods Patients older than 60 years, ASA II–III, with risk factors for or known coronary artery disease were enrolled in this randomized controlled study. Patients were randomized to conventional analgesia using opioid intravenous patient-controlled analgesia or continuous lumbar plexus block analgesia, both started preoperatively and maintained until postoperative day three. Continuous electrocardiogram monitoring with ST segment analysis was recorded. Serial cardiac enzymes and pain scores were registered during the entire period. We measured the incidence of ischemic events per subject registered by a continuous ST-segment Holter monitoring. Results Thirty-one patients (intravenous patient-controlled analgesia 14, lumbar plexus 17) were enrolled. There were no major cardiac events during the observation period. The number of ischemic events recorded by subject during the observation period was 6 in the lumbar plexus group and 3 in the intravenous patient-controlled analgesia group. This difference was not statistically significant (p = 0.618). There were no statistically significant differences in the number of cases with increased perioperative troponin values (3 cases in the lumbar plexus group and 1 case in the intravenous patient-controlled analgesia group) or in terms of pain scores. Conclusions Using continuous perineural analgesia, compared with conventional systemic analgesia, does not modify the incidence of perioperative cardiac ischemic events of elderly patients with hip fracture.